PENGARUH MOTIVASI KERJA DAN BEBAN KERJA TERHADAP KINERJA KARYAWAN (Studi Kasus pada PT. Kiyokuni High Precision Automotive Indonesia) - Sutrisno, Niantoro; Jaelani, Evan; Wijaya, Rina (JAB (Jurnal Akuntansi & Bisnis), 2020)
This study was aimed to determine the effect of work motivation towards the employee performance PT. Kiyokuni High Precision Automotive Indonesia, Effect of work load towards the employee performance of PT. Kiyokuni High Precision Automotive Indonesia, effect of work motivation and work load towards the employee performance of PT. Kiyokuni High Precision Automotive Indonesia. The sample in this study amounted to 74 respondents. Sampling technique using simple incidental technique. Data analysis method used descriptive analysis and regression analysis. Partial test result show that work motivation positively affects to the employee performance, work load positively affects to the employee performance. And the result of the research concluded that work motivation and work load have simultaneous positive influence on the employee performance. Â Keyword: work motivation, workload, employee performance